2016
DOI: 10.3758/s13414-016-1193-5
|View full text |Cite
|
Sign up to set email alerts
|

Does increasing the intelligibility of a competing sound source interfere more with speech comprehension in older adults than it does in younger adults?

Abstract: A previous study (Schneider, Daneman, Murphy, & Kwong See, 2000) found that older listeners' decreased ability to recognize individual words in a noisy auditory background was responsible for most, if not all, of the comprehension difficulties older adults experience when listening to a lecture in a background of unintelligible babble. The present study investigated whether the use of a more intelligible distracter (a competing lecture) might reveal an increased susceptibility to distraction in older adults. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…However, when auditory conditions were individually adjusted to compensate for sensory degradation, these differences were eliminated. In other words, older adults were able to perform as well as younger adults, even in a complex listening comprehension task, when sensory degradation was compensated for (for replication, see Lu et al 2016). These results may be further supported by a recent study indicating that younger adults with hearing impairment show equal cognitive performance to older adults with similar sensory decline (Verhaegen et al 2014).…”
Section: Comprehension: An Example Of the Effect Of Auditory Degradatmentioning
confidence: 56%
“…However, when auditory conditions were individually adjusted to compensate for sensory degradation, these differences were eliminated. In other words, older adults were able to perform as well as younger adults, even in a complex listening comprehension task, when sensory degradation was compensated for (for replication, see Lu et al 2016). These results may be further supported by a recent study indicating that younger adults with hearing impairment show equal cognitive performance to older adults with similar sensory decline (Verhaegen et al 2014).…”
Section: Comprehension: An Example Of the Effect Of Auditory Degradatmentioning
confidence: 56%
“…In another study conducted in an investigating the speech recognition performance of young and elderly people with normal hearing, it was reported that, the more meaningful the competing noise (competing noise was selected in three ways: part of the speech text, a bubble noise, and single person competing noise), the more the IM would occur. In this study, the poorer performance of the elderly people was attributed to the agerelated decline in their cognitive abilities in word recognition [43]. Some studies have examined the role of age in detecting target speech from competing speech.…”
Section: Elderly Peoplementioning
confidence: 84%
“…Auditory spatial training is designed based on five signs that are important in informational masking release: angular differentiation between target and competing signals 16, 3436 ; signal to noise ratio 34 ; similarity and difference between the target and competing signals 12 ; similar or different gender for target and competing signals 12, 37 ; and meaningfulness of the competing signal 12 . As one of the main principles of any auditory training program is progression in difficulty so the training sessions will be divided into three general steps by considering the competing signals.…”
Section: Protocolmentioning
confidence: 99%
“…Various studies have indicated that with an increase in age, side-effects of competing noises will increase 1, 1012 . Different studies have revealed that elderly populations, who do not have peripheral auditory impairment, suffer from diminished ability of using acoustic and phonetic signs to separate speech from background noise, compared to young people; therefore, more informational masking occurs in this population 10, 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation